ANALISIS KINERJA KARYAWAN DIVISI MILL DAN BOILER PT GULA PUTIH MATARAM - Sudibyo Sudibyo; Slamet Hartono; Azwar Maas (Agro Ekonomi, 2014)
The objectives of this study are to analyze the understanding of employee of Mill and Boiler Division, PT Gula Putih Mataram to employee performance factors and their impact on employee performance. Fifty two employees of Mill and Boiler Division are drawn purposively as the respondents. The data of employee understanding on job description, SOP, employee relation, KPI, technical aspect, and employee performance were collected from the respondent through interview using prepared questionnaire. Data of employee performance was collected from the office of PT GPM. The result of data analysis shows that the performance of chief, officer, and supervisor in Mill and Boiler Division is good at rate of 70-80 percent. Factors affecting employee performance are understandings of employee on job description and SOP and employee relation. The study suggests to improve understanding of employee on job description and SOP and employee relation.